2018
DOI: 10.3389/fmicb.2018.00999
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in Riparian Sediments: A Large-Scale Longitudinal Distribution Pattern and Response to Dam Construction

Abstract: Sediment microbes play major roles in riparian ecosystems; however, little is known about their longitudinal distribution pattern and their responses to dam construction, the most severe human disturbance in river basins. Here, we investigated the variability of sediment bacterial communities along a large-scale longitudinal gradient and between dam-controlled and dam-affected sites in riparian zone of the Lancang River, China. The abundance, activity and diversity of sediment bacteria gradually increased in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…A recent study on the Lancang River reported that the biogeographic pattern of bacterial community in riparian sediments largely differed between the upper‐middle reach sites and the downstream sites (Chen et al ., ). Similarly, both bacterial and fungal communities were significant different among the three river sections according to our NMDS and PERMANOVA results (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study on the Lancang River reported that the biogeographic pattern of bacterial community in riparian sediments largely differed between the upper‐middle reach sites and the downstream sites (Chen et al ., ). Similarly, both bacterial and fungal communities were significant different among the three river sections according to our NMDS and PERMANOVA results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, spatial isolation might also contribute to dispersal limitation of microbial community. Our recent study reported the strong impact of dam construction on the relative importance of spatial distance for bacterial distribution in riparian sediments of Langcang River (Chen et al ., ). For the river sediment, water depth increased drag, which may restrict the mobility of microbial populations and exchange between sediment grains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations